Pentingnya Pemeriksaan Kehamilan (ANC) di Puskesmas Pasar Rebo: Studi Potong Lintang Deskriptif - Krista Alya, Ravi; Albab, Ulul; Komarunisa, Komarunisa (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2025)
Introduction: Antenatal care (ANC) is vital for ensuring maternal and fetal health. This study aims to describe the maternal and fetal characteristics of pregnant women attending ANC services at Puskesmas Pasar Rebo from June 2023 to June 2024. Methods: A descriptive cross-sectional study was conducted on 140 pregnant women. Data were collected on maternal sociodemographic characteristics, obstetric history, and fetal parameters.Results: The average maternal age was 27 ± 5,3 years, with a mean height of 157 ± 5,6 cm, an average body mass index (BMI) of 25.5 ± 4,9 kg/m2. The mean upper arm circumference was 27,47 ± 3,4 cm. Obstetric history showed an average gravida of 2, parity 1, abortus 0. On average, women attended 7,27 ± 3,13 ANC visits. Out of the 140 patients, 27 were referred: 9 cases of previous cesarean section, 2 with hypertension, 5 malpresentations, 2 cases of fetal growth restriction, 2 with placental problems, 2 cases of intrauterine fetal death (IUFD), 4 with hemmorhagic in early pregnancy, and 1 case of gemelli pregnancy. Fetal assessments indicated an average crown-rump length (CRL) of 4.8 ± 1,3 cm in the first trimester, an average fetal heart rate (FHR) of 170 ± 8 bpm in the first trimester, and 142 ± 7 bpm in the third trimester. The estimated fetal weight (EFW) averaged 2293 ± 452 grams, and the average amniotic fluid index (AFI) with a single deepest pocket (SDP) measured 4.5 ± 1,3 cm.Conclusion: Routine antenatal care visit correlated significant in detecting high risks pregnancy cases needed to be referred to obstetrician. This study highlights the importance of regular ANC visits in detecting maternal and fetal complications in first and third trimester at Puskesmas Pasar Rebo.